Unravelling multi-level governance systems - Michael Zürn (British Journal of Politics and International Relations, 2020)
One of the most important features of the multi-level governance research programme is the parallel conceptualisation of the vertical and the horizontal relationships within multi-level governance systems. Different systems of multi-level governance are characterised by the relationships between political institutions on the same level (Are there many task-specific organisations?) and by the relationship between different levels (On which level do we see political communities?). By conceptualising scale and community in a substitutive way as Hooghe and Marks in tendency do, some of the potentials are lost. I put forward the suggestion that treating the two dimensions as independent would allow for an even fuller picture of the dynamics of politics in multi-level governance systems.
Keywords: 300; community; dynamics; multi-level governance; scale; types of MLG